2022
DOI: 10.17113/ftb.60.02.22.7478
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamins D, B9 and B12 with Obesity-Related Diseases and Oral Microbiota Composition in Obese Women in Croatia

Abstract: Research background. Oral microbiota has become an important factor in obesity, but its association with obesity-related diseases and serum 25-hydroxy vitamin D [25(OH)D] and B complex levels is still uncertain. The main aim of the paper was to determine variation in oral microbiota composition regarding vitamin status and obesity-related diseases in obese females from Croatia. We hypothesized that the prevalence of probiotic or pathogen bacteria in the oral cavity of obese women in Croatia depends on vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The results of our investigation align with certain studies documented in the current body of literature, while disparities also exist. To begin, it is widely recognized that a correlation exists between vitamin D deficiency and obesity (17,18). This phenomenon can be elucidated by vitamin D being retained within adipose tissue, given its liposolubility as a fat-soluble vitamin (2).…”
Section: Discussionmentioning
confidence: 99%
“…The results of our investigation align with certain studies documented in the current body of literature, while disparities also exist. To begin, it is widely recognized that a correlation exists between vitamin D deficiency and obesity (17,18). This phenomenon can be elucidated by vitamin D being retained within adipose tissue, given its liposolubility as a fat-soluble vitamin (2).…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent Candida infections of the vagina, anogenital area, regions under the breasts, and axillae often occur in individuals with obesity and type 2 diabetes (13). In the study of women with obesity and diabetes/prediabetes, the oral microbiota showed specifically increased levels of Candida species (16). In men, the folds of the prepuce and the coronal margin of the penis are prone to balanitis and phimosis (1).…”
Section: Fungal Infectionsmentioning
confidence: 99%
“…Obesity, which is defined as the excessive accumulation of body fat, presents considerable health hazards and has emerged as a significant issue in public health on a global scale [1]. The genesis of this condition is complex and involves a combination of genetic, behavioral, metabolic, and environmental variables.…”
Section: Introductionmentioning
confidence: 99%